Further Results on Ph-supermagic Trees - Tita Khalis Maryati; Otong Suhyanto; Fawwaz Fakhrurrozi Hadiputra (LPPM Institut Teknologi Sepuluh Nopember, 2023)
Let G be a simple, finite, and undirected graph. An H-supermagic labeling is a bijective map f : V(G) E(G) → {1,2,…,|V(G)|+|E(G)|} in which f(V) = {1,2,…,|V(G)|} and there exists an integer m such that w(H') = _v V(H') f(v) + _e E(H') f(e) = m, for every subgraph H' H in G. In this paper, we determine some classes of trees which have P_h-supermagic labeling.